STUDENT’S PERCEPTIONS OF ONLINE AND HYBRID LEARNING IN INDONESIAN LANGUAGE COURSES - Asih Andriyati Mardliyah; Amy Krisdiana (Indonesian language and literature education program Majapahit Islamic University, 2023)
In the educational sector, the presence of the corona virus has had a positive impact. This is because this virous has been able to change the system of education in Indonesia, which initially only uses face to face learning model in the classroom, starting to get to know the online learning model and the hybrid learning model. The aim of this research is to describe the students’ perceptions of the implementation between hybrid learning at Majapahit Islamic University and the implementation of the online learning model at Universitas Terbuka (UT). This reserarch is qualitative research with a descriptive approach. The researchers uses survey techniques as data collection. The researchers use Miles and Huberman's interactive analysis technique as data analyses, namely (1) data collection, (2) data reduction, (3) data verification, and (4) data display. The research results show that the students from Universitas Terbuka give positive response to online learning via e-learning, while the students from Universitas Islam Majapahit also give a positive response to hybrid learning.